FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBELIAN TIDAK TERENCANA PADA BISNIS RITEL TIP TOP CIPUTAT - Devita Qadrina Irawan, - (2019)
In the era of globalization now the business world is always developing rapidly. The development of the business encourages changes in patterns of human behavior, where in consuming goods and services, people demand practicality and comfort in meeting their needs. With the development of business and behavior patterns, Tip Top is present as one of the retail businesses in the supermarket category. This research was conducted to determine the factors that influence unplanned purchases at the Tip Top Ciputat retail business, especially in the factors of sales promotion, personal sales and store atmosphere. The population in this study were people who had shopped at Tip Top Ciputat. The sample size taken was 75 respondents, with a non probability sampling method specifically purposive sampling. Data collection is done through the distribution of questionnaires. The analysis technique used is the method of PLS (Partial Least Square) analysis. The results of this study indicate that sales promotion and personal sales have an significant influence on unplanned purchases, while store atmosphere has no effect and is not significant on unplanned purchases.